Awakening to equality a young white pastor at the dawn of civil rights - Lutze, Karl E. (University of Missouri Press, 2006)
"In 1945, Karl Lutze was a young white pastor assigned to an African American church in Muskogee, Oklahoma. His experiences ministering to Black congregations there and, later, in Tulsa provide a unique perspective on the early civil rights movement in Oklahoma and within the Missouri Synod of the Lutheran Church"--Provided by publisher.